ETIOLOGY AND PATHOGENESIS OF RETINAL VEIN OCCLUSION: THE ACTUAL STATE OF A PROBLEM - A. A. Krylova; I. V. Zapuskalov; O. I. Krivosheina (Бюллетень сибирской медицины)
The review presents the actual questions of the etiopathogenesis of central retinal vein occlusion and its branches. It was found that predictors of disease is a pathology of haemostasis, including asymptomatic gene mutations of coagulation factors and platelet receptors, chronic viral infections, rheumatological and oncological diseases, hypertension, metabolic disorders, smoking, physical inactivity, inflammatory diseases of the retinal and optic nerve, congenital and acquired abnormalities of retinal vascular, glaucoma.The article also focused on the reasons for the formation of a blood clot. This is damage to the vascular wall, slowing the speed of blood flow in the vessel, hypercoagulation and hypofibrinolysis. Prevailing theories of the pathogenesis of retinal vein occlusion are analyzed. This is mechanical and theory “coag- ulopathy” whose arguments and counterarguments are discussed in detail. In addition, patients with reti- nal vein occlusion are needed in a multidisciplinary approach to the treatment of this disease. It is to im- prove the clinical and functional results of therapy and prevent the case of retrombosis.